Analysis of Tax Collection on Revenue from Tax Arrears (Empirical Study at KPP Pratama Tampan) - Sagita, Kamala (First Ciera Publisher, 2023)
Tax is one form of state revenue that contributes the largest percentage compared to other income sectors such as oil and gas (oil and gas) and non-oil and gas. The success of a country in collecting taxes from its citizens will certainly benefit the economic stability of the country concerned. Sustainability of state revenues from the tax sector is needed because tax revenues are the main source of state revenue and expenditure budget revenues. This research method is quantitative research, quantitative research can be interpreted as a research method based on the philosophy of positivism, used to examine a particular population or sample, data collection using research instruments, quantitative/statistical data analysis, with the aim of testing the established hypothesis. at the end of the output, it can be seen that the constants and variables of Tax Collection are statistically larger. At the constant which is 0.06 and the variable Tax Collection which is 0.011, both of which are below 0.05. The tax collection variable has a Sig value of 0.011 (0.05) and concludes that tax collection has a partial effect on tax arrears receipts. The Sig value shows that 0.011 is below 5% which indicates that more and more people are aware of paying tax arrears. The constant coefficient value of 4.143 with a positive sign indicates that when it is assumed that there is no income and religiosity, then the people of Pekanbaru City are actually already obedient in paying taxes. Given the figure of sig 0.006 (below 5%) it means that the basic potential of the Pekanbaru community is indeed obedient to paying taxes.